The effect of neurofeedback training on balance performance and attention shifting in children with reading disorder - Neda Sadeghi Naeinipour; Mohammad Ali Nazari; Mehdi Alizade Zarei; Mohammad Kamali (Vesnu Publications, 2013)
Introduction: Reading impairment is a neurodevelopmental disorder with some deficits in cognition and motor skills. Neurofeedback, as a new treatment approach, can improve the functioning of individuals with the disorder through regulating electroencephalographic (EEG) abnormalities. The purpose of this study was to investigate the effectiveness of neurofeedback balance protocol on improving balance performance and attention shifting in children with reading disorders. Materials and Methods: In this 20-session single subject study, 4 children (1 female) aging 8 to12 years completed twelve 30-miniute neurofeedback sessions. Repeated were performed during the baseline, treatment and follow-up stages of the study by means of the 2nd subtest of BOTMP for balance performance and the Posner Paradigm for shifting attention. Results: The results showed that the effect of treatment on balance performance was high (Cohen's d > 0.8) in all subjects but one and that attention shifting were improved only in some cases. Conclusion: Consequently, neurofeedback balance protocol can improve balance and, to some extents, attention shifting in children with reading disorders. Keywords: Neurofeedback, Reading disorder, Balance, Attention shifting